Análise comparativa em relação ao custo e consumo de materiais entre alvenaria estrutural e estrutura de concreto armado para a estrutura de um edifício residencial de 8 pavimentos - Oliveira, Felipe Eduardo de Souza (Universidade Federal de São Carlos, 2023)
The current civil construction market is constantly looking for new technologies that efficiently meet its growing demand, especially housing. Companies in the sector seek to optimize construction in order to promote higher quality at a lower price. The choice of the structural system to be adopted in an enterprise is based directly on that. The main objective of this work was to carry out a comparative analysis in relation to the cost and consumption of materials between two structural systems: structural masonry and reinforced concrete. For this, an 8- story model residential building designed in structural masonry, resized for reinforced concrete, was analyzed in order to obtain information on cost and consumption of materials for each constructive system in order to comparatively analyze the two systems, providing indications for the choice of the most economical structural system. Based on the analyses, a saving of 14% was obtained in the use of the system in structural masonry, in relation to the structure of the enterprise
Comparative analysis in relation to cost and consumption of materials between masonry structural and concrete structure armed for the structure of a building 8 floor residential
Keywords: Alvenaria Estrutural; Concreto Armado; Análise comparativa; Custo e consumo de materiais; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL